THE IMPORTANCE OF GENDER EQUALITY IN THE EDUCATION OF CHILDREN IN THE FAMILY (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2023)
This article talks about the importance of gender equality in the process of upbringing in a family environment. The relationships of parents to each other, the principle of imitation in them, directly and indirectly influence the upbringing of the individual.